2000
DOI: 10.1001/archotol.126.6.790
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Source of Vibrio alginolyticus–Associated Otitis

Abstract: Otitis externa and otitis media are commonly encountered in clinical practice. We report an unusual case of otitis externa, which was caused by Vibrio alginolyticus, several months after saltwater exposure. Clinicians need to be aware of this unusual pathogen, especially in refractory cases of ear infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The reason for V. alginolyticus 's lack of virulence remains unclear. V. alginolyticus has been etiologically associated with cellulitis and acute otitis media or externa 3,6-10. As a whole, these infections have responded well to appropriate antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for V. alginolyticus 's lack of virulence remains unclear. V. alginolyticus has been etiologically associated with cellulitis and acute otitis media or externa 3,6-10. As a whole, these infections have responded well to appropriate antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…hydrophila and V. alginolyticus infections have been reported in association with wounds exposed to water. [3][4][5][6][7]14,16,17 However, the number of clinical reports and reviews concerning A. hydrophila or V. alginolyticus infections in clinical journals is limited. In this case, it was likely that both isolates of A. hydrophila and V. alginolyticus were originally associated with water in Hamana Lake, a brackishwater lake, in which fresh water from a river and sea water mix.…”
Section: Discussionmentioning
confidence: 99%
“…15 Human infections caused by V. alginolyticus include ear, soft tissue, and wound infections. 14,16,17 Recent reports 18 showed that 40% of V. alginolyticus isolated from the environment produce ␤-lactamases conferring resistance to ampicillin. Antibiotic resistance in V. alginolyticus is a significant problem for wound infections related to the aquatic environment.…”
mentioning
confidence: 99%
“…Symptoms include diarrhea, abdominal cramps, vomiting, fever, and skin lesions if infection enters through a wound [ 2 , 3 ]. There have been a few reports of V. alginolyticus causing otitis externa in patients with recent exposure to infested seawater, primarily limited to waters around Europe or the Mediterranean in the warmer times of the year [ 4 , 5 ]. The suspected pathogenesis is that the strain exerts cytotoxic effects on keratinocytes and HEI-OC1 cells by inhibiting cell proliferation and migration and inducing apoptosis and cell death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%